One-stop child enrichment and sports centre system - Kang, Sing Chee (2024)
Enrichment programs, encompassing sports clubs, martial arts, dance classes, academic lessons and other extracurricular activities played a vital role in children’s development. However, in Malaysia, parents face challenges in searching and comparing these activities due to the lack of a centralized platform. Therefore, the One-Stop Child Enrichment and Sports Centre System is introduced and aimed to fill this gap by offering a one-stop platform where parents can easily find suitable extracurricular activities for their children, while allowing service providers to advertise their programs. The system provides parents with a centralized platform to search, filter, compare and enrol in various enrichment programs and sports activities for their children. It also offers efficiency and visibility for activity providers to showcase their offerings and attract a wider audience. The system also implemented Single Sign-On (SSO) to ensure security and improve the user experience for parents. Moreover, the project utilized an iterative and incremental software development methodology, with initial planning followed by iterative phases of requirements gathering, analysis, design, implementation, testing, and evaluation. Besides, the development tools that used in this project are including Vue.js, Laravel, MySQL, Visual Studio Code and Pusher were employed to build the system. All objectives of this project have been successfully achieved, culminating in the development and implementation of the system, while several recommendations for future improvements also have been identified.